The wisdom of wolves : lessons from the Sawtooth pack - Dutcher, Jim, 1943-; Dutcher, Jamie; Manfull, James (National Geographic, 2018)
"From the world-famous couple who lived alongside a three-generation wolf pack, this book of inspiration, drawn from the wild, will fascinate animal and nature lovers alike. For six years Jim and Jamie Dutcher lived intimately with a pack of wolves, gaining their trust as no one has before. In this book the Dutchers reflect on the virtues they observed in wolf society and behavior. Each chapter exemplifies a principle, such as kindness, teamwork, playfulness, respect, curiosity, and compassion. Their heartfelt stories combine into a thought-provoking meditation on the values shared between the human and the animal world. Occasional photographs bring the wolves and their behaviors into absorbing focus"--